The Oxford handbook of political leadership - Rhodes, R. A. W.; Hart, Paul 't (Oxford University Press, 2014)
Political leadership has returned to the forefront of research in political science in recent years, after several years of neglect. This handbook provides a broad-ranging and cohesive examination of the study of political leadership.